Peningkatan Kualitas Perawatan Bayi dengan Berat Badan Lahir Rendah di Dusun Pengadok, Desa Mantang - Komalasari, Nova Silpia; Ningsih, Nining Fatria; Wahyuni, Ervin Dini (SAMBARA: Jurnal Pengabdian Kepada Masyarakat, 2025)
Neonatal mortality, particularly caused by low birth weight (LBW) infants, remains a significant health issue in many countries. This study aims to improve the quality of care for LBW infants through education for parents and the involvement of posyandu cadres in Dusun Pengadok, Desa Mantang. The methods used included providing education on LBW infant care techniques, such as kangaroo care and exclusive breastfeeding, as well as enhancing the role of posyandu cadres in monitoring and supporting families. The results of the community service showed a significant increase in the average weight gain of infants after the intervention, as well as improvements in care practices by parents. Furthermore, the involvement of posyandu cadres in monitoring the infant's development on a regular basis proved to be effective in improving care quality. Although there were some challenges, such as time constraints for working parents, these results demonstrate that collaboration between parents and posyandu cadres can improve the quality of care for LBW infants and potentially reduce infant mortality rates. This program provides an important contribution to improving the health of LBW infants and can be replicated in other areas with similar issues.